THE IMPOSSIBILITY OF REVIVING DINAR AND DIRHAM CURRENCY SYSTEM IN THE MODERN ECONOMY WORLD - Muflih, Muhammad (Journal of Indonesian Economy and Business, 2012)
This study proves that in the discourse of fiqh, Islamic history, and Islamic banking theÂ position of the concept of reviving the currency of dirham and dinar is very weak.Indicators that justify the conclusion of this study are: (1) there is a correspondence withÂ historical evidence of inflation in the Islamic world, (2) there is correspondence withÂ thoughts of fiqh, (3) there is a correspondence with modern syariah financial concept, andÂ (4) there is a correspondence with Islamic banking attitude.This study is written to challenge the idea of Ahmad Hasan, Hifzu Rab, Khan-Mirakhor, Meera-Larbani, and âUmar Vadillo who state that inflation problem in IslamicÂ world is best solved by reapplying the currencies of dinar and dirham as bases ofÂ transaction mediation. The inaccuracy of conclusion of the modern Islamic economistÂ figures was shown by many historical facts showing the turmoil in values of these two goldÂ bills in time of inflation. Other reasons for the fragility of these two currencies are;(i) lackÂ of support of the fiqh expert in strengthening these currency systems as way out of theÂ inflation-affected transaction, (ii)lack of support of fiqh experts to urge Islamic worlds toÂ use only dinar and dirham as official currency,(iii) lack of support of Islamic bankingÂ experts to revive the use of dinar and dirham as transaction bases and remedy forÂ inflation-affected transaction. The facts showed that the chosen system taken by fiqh andÂ Islamic banking experts in settling the inflation-affected transaction was the strengtheningÂ of muâÃ¢malah transaction system instead of alternating the currency system. The outcomeÂ of the strengthening the muâÃ¢malah transaction system is a concept of price adjustment.The concept of price adjustment gives a strong implication to modern Islamic banking asÂ an instrument of the muâÃ¢malah transaction system support when facing inflation cases.Keywords: inflation, islamic banking, dinar, dirham